Thermal and Mechanical Properties of Sn-8Zn-3Bi Solder Alloy - Duong, Ngoc Binh (JST: Engineering And Technology For Sustainable Development, 2021)
Thermal and mechanical properties of Sn-8Zn-3Bi solder alloy on copper substrate was evaluated via measuring the melting temperature, the coefficient of thermal expansion (CTE), the tensile and shear strength of the solder joint. The measured properties of the alloy then compared to the properties of the traditional and widely used eutectic Sn-37Pb solder alloy. The results show that the melting (liquidus) temperature of Sn-8Zn-3Bi was 195 °C, the CTE of Sn-8Zn-3Bi was 22.2 × 10⁻⁶ K⁻¹ in the temperature range of 30–130 °C. At the same testing condition, both tensile and shear strength of Sn-8Zn-3Bi joints were higher than those of Sn-37Pb. Stress-strain curve indicated that the Sn-8Zn-3Bi joints was brittle whilst the Sn-37Pb joints was ductile.